2011
DOI: 10.1002/art.30202
|View full text |Cite
|
Sign up to set email alerts
|

Berberine induces dendritic cell apoptosis and has therapeutic potential for rheumatoid arthritis

Abstract: Objective. To investigate the effects of berberine on dendritic cell (DC) apoptosis and its potential as a therapeutic agent in rheumatoid arthritis (RA).Methods. Bone marrow (BM)-derived myeloid DCs (MDCs) and plasmacytoid DCs (PDCs) were generated by culturing BM cells with granulocytemacrophage colony-stimulating factor/interleukin-4 or flt3L, respectively. Splenic DCs, T cells, and B cells were purified using a magnetic-activated cell sorting system. In vitro apoptosis was assessed by annexin V/propidium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 62 publications
(14 reference statements)
9
70
0
Order By: Relevance
“…And the relevant mechanisms deserve further study. Third, the co-treatment of a high concentration of BBR (100 lM) and 0.75 mM SNP could enlarge the toxic effect of BBR and reveal the rare effect of BBR on promoting apoptosis according to previous study [37]. In this study, the results of flow cytometry test and Western blot have demonstrated that BBR reversed SNPinduced chondrocyte apoptosis, and down-regulated the protein expressions of Bax and caspase-3, while up-regulated Bcl-2 expression in cultured chondrocytes.…”
Section: Discussionmentioning
confidence: 76%
“…And the relevant mechanisms deserve further study. Third, the co-treatment of a high concentration of BBR (100 lM) and 0.75 mM SNP could enlarge the toxic effect of BBR and reveal the rare effect of BBR on promoting apoptosis according to previous study [37]. In this study, the results of flow cytometry test and Western blot have demonstrated that BBR reversed SNPinduced chondrocyte apoptosis, and down-regulated the protein expressions of Bax and caspase-3, while up-regulated Bcl-2 expression in cultured chondrocytes.…”
Section: Discussionmentioning
confidence: 76%
“…Increasing evidence has shown that DCs may be attractive targets for the treatment of autoimmune diseases, such as RA (36,37). For instance, injection of immature DCs attenuates CIA by inducing in vivo expansion of CD49b + regulatory T cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…BBR also suppressed the expression of costimulatory molecules in DCs, which is in agreement with earlier findings in animals, which showed that BBR was able to downregulate the expression of CD80 and CD86 in mouse DCs stimulated by LPS. 19 A downregulated expression of costimulatory molecules on DCs may partially contribute to the observed impaired T-cell reactivity. Based on the study presented here and previous studies, it becomes evident that BBR can act as a negative modulator of the Th17 cell response via an effect on APCs, especially DCs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main active ingredients of these herbs, BBR also exhibits antitumor, antimicrobial, and even antidiabetic effects. [15][16][17][18] Recent reports have suggested that BBR may suppress inflammation in collagen-induced arthritis, an animal model for human rheumatoid arthritis, 19 experimental type I diabetes, 20 and experimental autoimmune encephalomyelitis, an animal model for human multiple sclerosis. 21,22 These findings raised the question of whether BBR could possibly also be applied in the treatment for clinical autoimmune uveitis.…”
mentioning
confidence: 99%